Pelatihan Teknik Merias Wajah Pesta Siang dan Pesta Malam - Burhanuddin, Izmi; Syamsidah, Syamsidah; Rosmiaty, Rosmiaty (Universitas Negeri Makassar, 2023)
The Course was given to the teenagers which was held in the Rammang-Rammang Tourism Village, Bontoa District, Maros Regency, South Sulawesi Province. Partner groups need training on makeup for day parties and evening parties, with problems including: 1) The participants do not understand properly and correctly how to apply each of the cosmetics materials, equipmentsand cosmetics which are used for day parties make-up and night parties make-up; 2) Partners as participants in training activities are generally used to using standard make-up equipment and materials but do not know and understand make-up techniques for day parties and night parties; 3) Participants do not know the difference of how to apply make-up for day parties and night parties so that it can be seen what occasion for the event used for the make-up technique for day parties and night parties. The Service Team started the training activity by explaining the function and application method of each Equipment and material which are used in make-up and followed upby discussion and question and answer with the participants, followed up by a tutorial on how to apply make-up for day and night parties. After the training, the following results are obtained: 1) Participants know and understand properly and correctly how to apply each of the cosmetics material, tools and cosmetics used in makeup for day and night parties; 2) Partners as participants in training activities generally already know how to use standard makeup equipment and materials and already know and understand make-up techniques for day parties and night parties; 3) All the participants already know the difference in how to apply make-up for day and night parties so that they can know the opportunity to apply make-up for day and night party Keywords: Course, make-up, day party, night party